Tri Pramana-based Differentiated Instruction to Enhance Higher Order Thinking and Emotional Engagement among Primary School Students - Dewa Made Dwicky Putra Nugraha; Ida Bagus Wisnu Parta; I Gusti Ayu Putu Istri Aryasuari (Universitas Pendidikan Ganesha, 2025)
Higher Order Thinking Skills (HOTs) and emotional engagement among elementary school students remain low due to the suboptimal implementation of differentiated instruction and the limited integration of local wisdom in classroom practices. This condition indicates that cognitive development has not been fully connected to meaningful and contextual learning experiences. This study aims to analyze and examine the effectiveness of Tri Pramana based differentiated instruction in enhancing students’ HOTs and emotional engagement. The study employed a quasi experimental design with a mixed methods approach. The participants consisted of 117 fifth grade students divided into experimental and control groups. Quantitative data were collected using validated instruments, namely a HOTs test and an emotional engagement questionnaire, while qualitative data were obtained through structured interviews with teachers and students. Quantitative data were analyzed using descriptive statistics and MANOVA to test the simultaneous effect of the intervention. The results show that the experimental group achieved significantly higher mean scores in both HOTs and emotional engagement compared to the control group. The MANOVA results confirmed a simultaneous and significant effect of Tri Pramana based differentiated instruction on both variables. The qualitative findings supported these results by indicating improvements in students’ cognitive reasoning and active participation. This study implies that integrating local wisdom based frameworks into differentiated instruction can strengthen cognitive and affective learning outcomes simultaneously.